A potential mechanism by which torque output is preserved in cerebral palsy during fatiguing contractions of the knee extensors. Issue 2 (17th November 2015) - Moreau, Noelle G.; Knight, Heather; Olson, Michael W.
ABSTRACT: Introduction : The purpose of this study was to compare agonist and antagonist electromyography (EMG) during an isokinetic fatigue protocol in subjects with cerebral palsy (CP) and typical development (TD). Methods : Nine individuals with CP and 11 with TD completed 50 repetitions of maximum concentric knee extensions (KE) and flexions (KF) at 60°/second. Results : Rate of decline in peak torque for KE was significantly less in CP compared with TD. Rate of decline in agonist EMG was not significantly different between groups, but the rate of decline in antagonist EMG was significantly greater in CP. There were no differences between groups for KF. Conclusions : Declining agonist EMG occurred in parallel with declining antagonist hamstring activity in CP, decreasing the relative opposing force and resulting in a lesser decline in net torque. This finding illustrates a potential mechanism by which net torque is preserved in those with CP who are inherently weaker. Muscle Nerve 53: 297–303, 2016